2022
DOI: 10.1108/ir-11-2022-0279
|View full text |Cite
|
Sign up to set email alerts
|

The role of machine learning in robotics

Abstract: Purpose This paper aims to illustrate the growing role of machine learning techniques in robotics. Design/methodology/approach Following an introduction which includes a brief historical perspective, this paper provides a short introduction to machine learning techniques. It then provides examples of robotic machine learning applications in agriculture, waste management, warehouse automation and exoskeletons. This is followed by a short consideration of applications in future generations of self-driving vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In addition, as such systems are able to overcome the inconsistencies associated with human eye standards, they can be customized to meet higher digital standards in industrial quality control and achieve performance levels beyond the limits of the human eye with respect to speed, spectrum recognition, resolution, sensitivity, and reliability. In short, the introduction of machine vision has greatly improved automation and intelligence on production lines [13,14]. Zhao [15] used the SIFT algorithm, Kalman filtering algorithm, and updating the size of the kernel window width to study the algorithm for target tracking of train hooks based on vision, and the results of the video tracking run concluded that the use of target tracking algorithms can be adapted to the working environment of the train-hook picking robot.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as such systems are able to overcome the inconsistencies associated with human eye standards, they can be customized to meet higher digital standards in industrial quality control and achieve performance levels beyond the limits of the human eye with respect to speed, spectrum recognition, resolution, sensitivity, and reliability. In short, the introduction of machine vision has greatly improved automation and intelligence on production lines [13,14]. Zhao [15] used the SIFT algorithm, Kalman filtering algorithm, and updating the size of the kernel window width to study the algorithm for target tracking of train hooks based on vision, and the results of the video tracking run concluded that the use of target tracking algorithms can be adapted to the working environment of the train-hook picking robot.…”
Section: Introductionmentioning
confidence: 99%